C-prenylation of 1,3 dihydroxyxanthone: synthesis, characterization and antibacterial activity - Yuanita, Emmy; Jannah, Baiq Khaeratul; Ulfa, Maria; Sudirman; Ningsih, Baiq Nila Sari; Dharmayani , Ni Komang Tri (Acta Chimica Asiana, 2023)
Prenylated 1,3-dihydroxyxanthone has been successfully synthesized using Prenyl bromide and KOH. Characterization of the synthesized compound using Infra Red (IR) and Nuclear Magnetic Resonance (1H-NMR) showed that monosubstituted c-prenylation was occurred at carbon number 2 to form 1,3-dihydroxy-2-prenylxanthone. The synthesis result was a yellow-brown paste with a yield of 43.09%. This prenylated 1,3-dihydroxyxanthone had moderate antibacterial activity against Escherichia coli with an inhibition zone > 5 mm at a concentration of 15%.